Health care challenges and human resources for health in Thailand : migrations, social and political tensions, and human rights implications - Thoresen, Stian Ho Yong (Curtin University, 2008)
The global shortage of human resources for health and the brain drain of health care professionals exacerbate health care challenges in many small and medium sized economies, including efforts to curb the HIV/AIDS pandemic. This research investigated attitudes, perceptions, and dynamics among health care students and professionals in Thailand related to human resources for health, migration, inequitable distribution between rural and urban areas as well as between the public and private sector, and influences on migration ambitions. This included contemporary social and political parameters. Perceptions and attitudes among health care students and professionals were explored through a questionnaire survey and semi-structured interviews with health care professionals. Additional interviews with key-informants encapsulated contemporary events, dynamics, adversities, and challenges specific to the Thai context. It is argued that both the right to health care and health care professionals’ right to free movement must be protected and upheld. This research adds to the knowledge and insight into the specific health care challenges in Thailand and reflections upon the sustainability of the health care system; both in light of these health care challenges and the principles of sustainability as proposed by The World Commission on Environment and Development, the Brundtland Report (1990). It will enhance the scope from which health care, manpower expansion, and reform is pursued. Any approach to stem the exodus of health care professionals must recognise the rights of all stakeholders, including health care professionals and health care consumers, and all stakeholders must be engaged in the pursuit of sustainable health care through the principles of sustainable development and global sustainability.